Regulation of gambling in Nigeria: a need to review the status quo (2018)
Gambling is a phenomenon that has not been given adequate attention in Nigeria. If properly handled it constitutes money spinning venture to the government. The legal and regulatory control of gambling in Nigeria appears to be clumsy and grossly inadequate. The traditional method of gambling in Nigeria has not been properly managed and the licensing provisions are very conflicting. The nascent internet and mobile technologies have also provided new methods of gambling which create a tensed atmosphere for the control of gambling activities especially due to the seamless operations of these technologies. Countries like the US, UK and Australia have made spirited efforts in order to tame interactive gambling within their jurisdictions. A review of the approaches of these jurisdictions will serve as a direction for Nigeria which has not taken cognisance of the special challenges occasioned by the interactive form of gambling. This paper seeks to address in general the legal and regulatory challenges of gambling in Nigeria.